2003
DOI: 10.1016/j.rapm.2003.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Is skin disinfection with 10% povidone iodine sufficient to prevent epidural needle and catheter contamination?

Abstract: Our results suggest that despite skin surface disinfection with PI, there is still significant risk for contamination of needles and catheters during epidural catheterization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 16 publications
1
10
0
3
Order By: Relevance
“…Extrinsic sources of infection include invasion of skin bacteria through a needle tract, [14][15][16][17][18] contaminated syringes, 19 catheter hubs, 20 local anesthetics, 21 or breaches in aseptic technique. [21][22][23][24] The migration of skin bacteria through needle puncture sites is considered to be a major source of epidural colonization.…”
Section: Sources Of Injectionmentioning
confidence: 99%
“…Extrinsic sources of infection include invasion of skin bacteria through a needle tract, [14][15][16][17][18] contaminated syringes, 19 catheter hubs, 20 local anesthetics, 21 or breaches in aseptic technique. [21][22][23][24] The migration of skin bacteria through needle puncture sites is considered to be a major source of epidural colonization.…”
Section: Sources Of Injectionmentioning
confidence: 99%
“…(4) Sonuç olarak pek çok çalışmada, cildin bariyer özelliğini bozan bu girişimler için asepsi kurallarına göre cilt dezenfeksiyonu uygulandığında ve sağlıklı bireylerde kısa süreli kullanıldığında bile epidural kateterler ile iğneler mikrobiyolojik olarak incelendiğinde, üzerlerinde mikroorganizmaların kolonize olduğu gösterilmiştir. (5,6) Bu durum cilt dezenfeksiyonunda kullanılan alkol, povidon-iyot ve klorheksidin, propanol ve benzalkonyum klorür içeren çok sayıda antiseptik solüsyonun, epidural kateter ve iğnedeki kolonizasyonu azaltmadaki etkinliklerinin incelenmesine neden olmuştur. (5,7,8) Ancak, epidural kateter kolonizasyonunu önlemede cildin antisepsisi için hangi antiseptik solüsyonun en iyi olduğu konusunda henüz düşünce birliği yoktur.…”
Section: Introductionunclassified
“…Epidural needle contamination could be as high as 25% and multiple entries could theoretically results in a higher rate of infection[30]. However, there is no evidence that multiple attempts could cause an epidural abscess[30],[31]. One study with multiple skin passes with epidural needles showed no increased epidural infection up to 5 d post-procedure follow-up[30].…”
Section: Discussionmentioning
confidence: 99%